Characteristics of suicidal attacks in pregnancy; a multicenter study. (2nd October 2022) - Akgün Kavurmaci, Seda; Hortu, İsmet and Ilgen, Orkun and Gülbahar, Ayşegül
Abstract: Background: Maternal death, fetal death and suicidal attack (SA), each one of these topics are an important public health problem. A suicide attack attempt during pregnancy includes all these important issues together and requires additional attention. Some factors may show regional differences such as suicidal method, distribution of attempts according to the gestational week and the most common preferred drugs. The predetermination of these variables may allow taking preventive measures and advantages can be gains on maternal-fetal health. Methods: The data of pregnant women who were admitted to 3 different university hospital emergency departments in same city between 2015 and 2020 after a SA was investigated. SAs features and distribution of attacks based on variables such as age, gravidity and gestational week etc. was recorded. In addition, obstetric/non-obstetric injuries and pregnancy outcomes was also analyzed. Results: The mean age of 78 cases was 26.9 ± 6.4 (17–44) years. SAs were detected most frequently in the 1st trimester (42.3%) and at least in the 3rd trimester (20.5%). The most preferred SA method (89.7%) was high-dose drug intake. The most commonly preferred drugs were paracetamol, iron/folic acid replacement therapy drugs and antidepressants. Conclusions: Pregnant women are at risk of SA, especially in the first trimester. Contrary to popular belief, 75% of pregnant women who have SA do not have a known psychiatric disease diagnosis before. Therefore, psychiatric evaluation should be a part of routine pregnancy follow-up examination, especially in the first trimester. In this way, pregnant women which have increased risk factors for SA such as alcohol addiction, unwanted pregnancy, and depressive mood can be detected early. In this special patient group, the most commonly SA method is high-dose drug intake. Knowing the high dose treatments for frequently used drugs such as paracetamol by emergency physicians and obstetricians, educating medical staff about treatments can save additional time for mother and fetus and can be a life saver approach.